Gout Can Increase the Risk of Receiving Rotator Cuff Tear Repair Surgery. (August 2017) - Huang, Shih-Wei; Wu, Chin-Wen; Lin, Li-Fong; Liou, Tsan-Hon; Lin, Hui-Wen
Background: Gout commonly involves joint inflammation, and clinical epidemiological studies on involved tendons are scant. Rotator cuff tears are the most common cause of shoulder disability, and surgery is one of the choices often adopted to regain previous function. Purpose: To investigate the risk of receiving rotator cuff repair surgery among patients with gout and to analyze possible risk factors to design an effective prevention strategy. Study Design: Cohort study; Level of evidence, 3. Methods: The authors studied a 7-year longitudinal follow-up of patients from the Taiwan Longitudinal Health Insurance Database 2005 (LHID2005). This included a cohort of patients who received a diagnosis of gout during 2004-2008 (gout cohort) and a cohort matched by propensity scores (control cohort). A 2-stage approach that used the National Health Interview Survey 2005 was used to obtain missing confounding variables from the LHID2005. The crude hazard ratio (HR) and adjusted HR were estimated between the gout and control cohorts. Results: The gout and control cohorts comprised 32, 723 patients with gout and 65, 446 people matched at a ratio of 1:2. The incidence of rotator cuff repair was 31 and 18 per 100, 000 person-years in the gout and control cohorts, respectively. The crude HR for rotator cuff repair in the gout cohort was 1.73 (95% confidence interval [CI], 1.23-2.44; P < .01) during the 7-year follow-up period. After adjustment for covariates by use of the 2-stage approach, the propensity score calibration-adjusted HR was 1.60 (95% CI, 1.12-2.29; P < .01) in the gout cohort. Further analysis revealed that the adjusted HR was 1.73 (95% CI, 1.20-2.50; P < .001) among patients with gout who did not take hypouricemic medication and 2.70 (95% CI, 1.31-5.59; P < .01) for patients with gout aged 50 years or younger. Conclusion: Patients with gout, particularly those aged 50 years or younger and without hypouricemic medication control, are at a relatively higher risk of receiving rotator cuff repair surgery. Strict control of uric acid levels with hypouricemic medication may effectively reduce the risk of rotator cuff repair.